2023
DOI: 10.3389/fpls.2023.1174985
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of QTLs for oil content in four maize DH populations

Abstract: Oil is one of the main components in maize kernels. Increasing the total oil content (TOC) is favorable to optimize feeding requirement by improving maize quality. To better understand the genetic basis of TOC, quantitative trait loci (QTL) in four double haploid (DH) populations were explored. TOC exhibited continuously and approximately normal distribution in the four populations. The moderate to high broad-sense heritability (67.00-86.60%) indicated that the majority of TOC variations are controlled by gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
2
1
Order By: Relevance
“…Furthermore, the near-ubiquitous distribution of QTLs associated with grain starch content across most chromosomes, except for chromosomes 9 and 10, highlights the genetic complexity underlying grain starch content in maize. These findings diverge slightly from those obtained by Zhang et al (2023) , who utilized different genotypes from the ones in our study and detected a combined total of 16 QTLs for grain oil content distributed across all maize chromosomes. Yang et al (2012) also identified 58 QTLs for kernel oil content in all chromosomes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the near-ubiquitous distribution of QTLs associated with grain starch content across most chromosomes, except for chromosomes 9 and 10, highlights the genetic complexity underlying grain starch content in maize. These findings diverge slightly from those obtained by Zhang et al (2023) , who utilized different genotypes from the ones in our study and detected a combined total of 16 QTLs for grain oil content distributed across all maize chromosomes. Yang et al (2012) also identified 58 QTLs for kernel oil content in all chromosomes.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we used linkage mapping to identify significant QTLs associated with grain quality traits in DH and F 3 tropical maize populations grown in Kenya. Numerous studies have extensively explored the genetic underpinnings of maize grain quality traits, resulting in the detection of a multitude of QTL ( Li et al, 2009 ; Guo et al, 2013 ; Galić et al, 2017 ; Karn et al, 2017 ; Badu-Apraku et al, 2020 ; Ndlovu et al, 2022 ; Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation